Inzidenzielle pulmonale Rundherde: Differenzialdiagnostik und Vorgehen = Incidental pulmonary nodules : differential diagnosis and clinical management - Baum, Philip; Schlamp, Kai; Klotz, Laura Valentina; Eichhorn, Martin E.; Herth, Felix; Winter, Hauke (Deutsches Ärzteblatt, 2024)
More than 1.5 million computerized tomographic (CT) scans of the chest and approximately 13 million chest X-rays are obtained in Germany each year, and incidental pulmonary nodules are commonly found (1). The number of chest CTs can be expected to...